170k views
3 votes
Can anyone explain how this question is done! Thank you soo much!

Can anyone explain how this question is done! Thank you soo much!-example-1

1 Answer

3 votes

Answer:

Apply the Quadratic Formula

x = -b±√b²-4ac/[2a]

a=1

b=–5

c=3

Substituting these

x = –(–5) ±√5²-4x1x3/[2(1)]

x= 5 ± √25-12/[2]

x= 5 ± √13/[2]

SO WE HAVE 2SOLUTIONS

x= 5+√13 /[2] and 5–√13 /[2]

The question asked for the smaller solution

It can't be the first because the first is an addition

The smaller solution would be

x= 5–√13/[2]

OPTION C

User Vishnuraj V
by
5.0k points